2022
DOI: 10.1093/eurheartj/ehac641
|View full text |Cite
|
Sign up to set email alerts
|

JCAD promotes arterial thrombosis through PI3K/Akt modulation: a translational study

Abstract: Aims Variants of the junctional cadherin 5 associated (JCAD) locus associate with acute coronary syndromes. JCAD promotes experimental atherosclerosis through the large tumor suppressor kinase 2 (LATS2)/Hippo pathway. This study investigates the role of JCAD in arterial thrombosis. Methods and results JCAD knockout (Jcad−/−) mice underwent photochemically induced endothelial injury to trigger arterial thrombosis. Primary huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…17 The JCAD level in plasma samples from patients with ST-elevation myocardial infarction was higher than that in controls. 17 Although these current studies suggest that JCAD promotes endothelial dysfunction and triggers expression of proinflammatory genes in blood endothelial cells, 25 the function of JCAD in perineurium is unknown. Endoneurial microvessels are in direct communication with circulating blood and are considered to be blood–nerve barriers, while the perineurium restricts passive diffusion of interstitial fluid from the epineurium into the endoneurium and vice versa.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…17 The JCAD level in plasma samples from patients with ST-elevation myocardial infarction was higher than that in controls. 17 Although these current studies suggest that JCAD promotes endothelial dysfunction and triggers expression of proinflammatory genes in blood endothelial cells, 25 the function of JCAD in perineurium is unknown. Endoneurial microvessels are in direct communication with circulating blood and are considered to be blood–nerve barriers, while the perineurium restricts passive diffusion of interstitial fluid from the epineurium into the endoneurium and vice versa.…”
Section: Discussionmentioning
confidence: 95%
“…25 Recently, JCAD has been reported to possibly promote arterial thrombosis. 17 The JCAD level in plasma samples from patients with ST-elevation myocardial infarction was higher than that in controls. 17 Although these current studies suggest that JCAD promotes endothelial dysfunction and triggers expression of proinflammatory genes in blood endothelial cells, 25 the function of JCAD in perineurium is unknown.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…An aberrant activation of the coagulation cascade results in an excessive generation of thrombi, impeding proper blood flow. Consequently, in the context of IPF, compromised perfusion due to thrombi exacerbates the condition, leading to impaired pulmonary circulation and ensuing hypoxia (Liberale et al., 2023). Moreover, the dysregulation of coagulation factors and fibrinolytic agents contributes to undue collagen buildup and scar tissue formation (Zhu et al., 2023).…”
Section: Dicussionmentioning
confidence: 99%
“…From zebrafish to humans, the sequence of JCAD is highly conserved in vertebrates indicating that the protein might have important functions in pathophysiology. The role of JCAD has been identified in pathological process of coronary artery disease 6 as well as arterial thrombosis 7 . Our previous work revealed that JCAD was significantly increased in steatohepatitis‐associated hepatocellular carcinoma specimens, and promoted hepatoma cells and their derived xenografts proliferation and growth 8 .…”
Section: Introductionmentioning
confidence: 99%